Resident Immune Cells of the Liver in the Tumor Microenvironment - Lu, Yunjie; Ma, Shiying; Ding, Wei; Sun, Pengcheng; Zhou, Qi; Duan, Yunfei; Sartorius, Kurt (Frontiers in Oncology, 2022)
The liver is a central immunomodulator that ensures a homeostatic balance between protection and immunotolerance. A hallmark of hepatocellular carcinoma (HCC) is the deregulation of this tightly controlled immunological network. Immune response in the liver involves a complex interplay between resident innate, innate, and adaptive immune cells. The immune response in the liver is modulated by its continuous exposure to toxic molecules and microorganisms that requires a degree of immune tolerance to protect normal tissue from damage. In HCC pathogenesis, immune cells must balance a dual role that includes the elimination of malignant cells, as well as the repair of damaged liver tissue to maintain homeostasis. Immune response in the innate and adaptive immune systems extends to the cross-talk and interaction involving immune-regulating non-hematopoietic cells, myeloid immune cells, and lymphoid immune cells. In this review, we discuss the different immune responses of resident immune cells in the tumor microenvironment. Current FDA-approved targeted therapies, including immunotherapy options, have produced modest results to date for the treatment of advanced HCC. Although immunotherapy therapy to date has demonstrated its potential efficacy, immune cell pathways need to be better understood. In this review article, we summarize the roles of specific resident immune cell subsets and their cross-talk subversion in HCC pathogenesis, with a view to identifying potential new biomarkers and therapy options.